First-principles calculations on Fe-Pt nanoclusters of various morphologies - Platonenko, Alexander; Piskunov, Sergei; Bocharov, Dmitry; Zhukovskii, Yuri F.; Evarestov, Robert A.; Bellucci, Stefano (Nature Publishing Group, 2017)
Bimetallic FePt nanoparticles with L1 0 structure are attracting a lot of attention due to their high magnetocrystalline anisotropy and high coercivity what makes them potential material for storage of ultra-high density magnetic data. FePt nanoclusters are considered also as nanocatalysts for growth of carbon nanotubes of different chiralities. Using the DFT-LCAO CRYSTAL14 code, we have performed large-scale spin-polarized calculations on 19 different polyhedral structures of FePt nanoparticles in order to estimate which icosahedral or hcp-structured morphology is the energetically more preferable. Surface energy calculations of all aforementioned nanoparticles indicate that the global minimum corresponds to the nanocluster possessing the icosahedron "onion-like" structure and Fe43Pt104 morphology where the outer layer consists of Pt atoms. The presence of the Pt-enriched layer around FePt core explains high oxidation resistance and environmental stability, both observed experimentally.
Financial support provided by Scientific Research Project for Students and Young Researchers Nr. SJZ/2016/17 implemented at the Institute of Solid State Physics, University of Latvia, is greatly acknowledged. A.P. and R.E. express their gratitude to High-performance computer centers of ISSP (University of Latvia) and St. Petersburg University. This research was partially supported by Graphene Flagship GrapheneCore1-AMD-696656-4.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics